Hospital Management Information System Usefulness in The Health Services Industry at Indonesia: Mandatory or Voluntary? - Victor Livinus; M.F. Arrozi Adhikara; Rokiah Kusumapradja (Universitas Muhammadiyah Yogyakarta, 2021)
This study aiming to obtain empirical evidence of usefulness, ease of use, Computer Self-Efficacy (CSE), and intend to use towards Actual Technology Use (ATU) as an issue of high complexity of healthcare organizations services. We use causality explanatory research for hypothesis testing with quantitative approach as methods. Data were analyzed by Path Analysis. Result is Perceived Usefulness (PU) had positive effect on Behavioral Intention to Use (BITU). Perceive Ease of Use (PEOU) had significant positive effect on ATU. The Conclusion is BITU is an intervening variable that can mediate the effect of PU toward ATU. These findings suggested that there is mandatory behavior toward users to apply Hospital Management Information System (HMIS).